Realizacja prawa do prywatności w rozumieniu poszanowania życia rodzinnego i wykonywania opieki rodzicielskiej w warunkach ubóstwa. Uwagi na gruncie wybranych norm prawa międzynarodowego publicznego i Europejskiej konwencji praw człowieka - Ćmikiewicz, Marta (Studia Prawa Publicznego, 2024)
Interference in family life is a particular form of threat to poor families, especially when the only impetus for state action in the form of an interference in the right to privacy is the poor material situation of the family. The article reflects on the possible threats to the realisation of family life within the framework of the right to privacy established under public international law, in particular the International Covenant on Civil and Political Rights, the Convention on the Rights of the Child and the European Convention on Human Rights (ECHR). In the view of the Human Rights Committee, the family should be oriented towards enabling the child to remain in the care of his or her parents or to return to their care or to other family members. The Committee on the Rights of the Child points out that the implementation of the right to privacy prohibits the recognition of material poverty as a basis and justification for taking a child out of parental care and into foster care. The European Court of Human Rights case law presented in the article confirms that children from poor families are at risk of being taken away from their parents and placed in foster care due to the financial status of the family, which may constitute a violation of the Article 8 of the ECHR. The fact that state authorities wrongly equate the lack of sufficient resources to support the family with child neglect poses a threat to the family life of poor individuals. Victims of violations of family bonds through harm to the private lives of family members should be protected under the human rights system. The following analysis makes it possible to identify the relevant problems from the point of view of the impoverished person or/and family, such as the questioning of parental capacity as a consequence of the erroneous equation of poverty with child neglect, or the withdrawal of the right to material assistance, all of which affect the realisation of family life, and further enables the identification of legal remedies for protection.